Additive Effect of the Combined Administration of Low Molecular Weight Heparin and Recombinant Hirudin on Thrombus Growth in a Rabbit Jugular Vein Thrombosis Model - Biemond, Bart J; Levi, Marcel; Nurmohanned, Michael T; Büller, Harry R; ten Cate, Jan W (Thrombosis and Haemostasis, 1994)
Recombinant Hirudin (r-Hirudin) is a new anticoagulant with specific antithrombin activity independently of antithrombin III. Low molecular weight heparins (LMWH) exert predominantly anti-Xa activity. Therefore, we hypothesized that combined administration of r-Hirudin and LMWH would induce a stronger antithrombotic effect as compared to r-Hirudin administered alone or combined with unfractionated heparin. To assess the effect on thrombus growth, we determined the accretion of l25I-labeled fibrinogen onto autologous non-radioactive thrombi preformed in the jugular veins of rabbits. The rabbits received unfractionated heparin (80 anti-factor Xa U), LMWH (80 anti-factor Xa U) or r-Hirudin (0.3, 5.0 and 10.0 mg/kg) either separately or by combined infusion for a 3 h period.R-Hirudin reduced the thrombus growth in a dose dependent fashion. The combined administration of 80 anti-Xa U LMWH and r-Hirudin at a dose of 0.3 mg/kg resulted in a stronger antithrombotic effect as compared to the combined infusion of unfractionated heparin and r-Hirudin (thrombus growth: 14.3% ± 6.0 vs 28.9% ± 6.5; p = 0.001). This difference in additive antithrombotic effect of 80 anti-Xa ULMWH versus unfractionated heparin on r-Hirudin was also observed when LMWH was combined with 5.0 mg/kg and 10.0 mg/kg r-Hirudin versus unfractionated heparin combined with r-Hirudin (thrombus growth: 16.4% ± 1.6 vs 29.1% ± 3.9; p = 0.01 and 10.1% ± 1.8 vs 20.4% ± 4.5; p = 0.001, respectively).In conclusion, this study showed an additive antithrombotic effect of LMWH on the thrombus growth reducing effect of r-Hirudin. This may potentially be of clinical interest, i. e. much lower doses of r-Hirudin may be used to achieve a similar effective anticoagulant effect when combined with LMWH.